Measurement of Maximal Oxygen Uptake (VO2Max) as a Cardiorespiratory Physiological Fitness Parameter Using Sensor Technology-Based Device Development (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: This study aims to measure the maximal oxygen uptake (VO2Max) as a cardiorespiratory physiological fitness parameter using the development of a sensor technology-based tool.Methods: This study uses a research and development design (Research And Development). Validation is carried out by competent experts. In this study, the researchers asked for validation from three experts, namely IT (electronics) experts, test and measurement experts and Sports Physiology experts (maximum oxygen volume). A total of 19 male and 11 female adults participated in this study. The usage trial was carried out using the expert validity method with an assessment using a questionnaire, test and retest. The data analysis technique used is r-correlationResult: Based on expert validation tests, the reliability, practicality, and effectiveness of the development of test instruments based on sensor technology can be used to measure VO2Max and provide accurate and effective results.Conclusion:The development of a test instrument based on sensor technology can provide accurate and effective results for measuring maximal oxygen uptake (VO2Max) as a cardiorespiratory physiological fitness parameter. This tool provides advances for monitoring VO2Max routinely in daily life, especially for carrying out training programs for athletes without the need for trained personnel and special equipment and expensive costs.
Keywords: VO2Max,Cardiorespiratory,Sensor Tecnology